PARE0001 Growing stronger together: implementing eular young pare's strategy. (15th June 2017) - Andersen, J; Balazova, P; Boyd, P; Olsder, W; Ostuzzi, S; Papastavrou, T; Stones, SR; Wilhelmer, T; Nieuwkoop, L Van; Caeyers, N; Klett, F
Abstract : Background: In a recent European youth survey, 53% reported that rheumatic and musculoskeletal diseases (RMDs) affected their ability to work, while 75% reported that RMDs interrupted their education. Therefore, in 2017 and 2018, while continuing to achieve the objectives reached in 2015 and 2016, EULAR Young PARE will focus on two key points from EULAR Young PARE's strategic objectives: work and education. Objectives: In 2017, in line with EULAR's efforts to raise awareness of the needs of people with RMDs among employers and other stakeholders, the specific and still unmet needs of young people with RMDs will be highlighted, so that employers and other stakeholders will be more aware of the needs of young people with RMDs and young people will receive better support to find a suitable job. In 2018, education for young people with RMDs will be in focus, so that educational institutions across Europe will be more flexible and assistive in supporting high quality education for young people with RMDs. Methods: In 2017, we will support EULAR's lobbying activities by raising awareness among employers and other stakeholders about the needs of young people with RMDs. We will also provide information to support young people in finding suitable jobs and to be aware of their rights in the workplace. Best practices concerning ergonomics, support programmes, career counselling and suitable jobs will be collected and shared. In 2018, we will support educational institutions across Europe to be more flexible and assistive in providing high quality education for young people with RMDs by offering training and support to national youth leaders. Results: Thanks to the results achieved in 2015 and 2016, it is anticipated that structures will be in place to continuously raise awareness among employers, medical staff in schools, teachers and unions about the competencies and limitations of young people with RMDs. These activities enable EULAR Young PARE to expand and strengthen the active network of youth groups across Europe. Every PARE organisation will have a PARE youth liaison person, who will be encouraged and supported to take active roles in their national organisations and in the EULAR community. Conclusions: The objectives reached by EULAR Young PARE in 2015 and 2016 are closely related to its future aims and achievements, allowing EULAR Young PARE to grow stronger and continue its work by the side of young people with RMDs, in order to improve their quality of life. References: EULAR Young PARE. Available from: http://www.youngpare.org [accessed on 30 January 2017]. Acknowledgements: Special thanks to EULAR and EULAR PARE for supporting the vision of EULAR Young PARE. EULAR Young PARE would also like to acknowledge all of the patient organisations that they continue to work with. Disclosure of Interest: None declared